If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (5x + 3) * 7 = 0 Reorder the terms: (3 + 5x) * 7 = 0 Reorder the terms for easier multiplication: 7(3 + 5x) = 0 (3 * 7 + 5x * 7) = 0 (21 + 35x) = 0 Solving 21 + 35x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-21' to each side of the equation. 21 + -21 + 35x = 0 + -21 Combine like terms: 21 + -21 = 0 0 + 35x = 0 + -21 35x = 0 + -21 Combine like terms: 0 + -21 = -21 35x = -21 Divide each side by '35'. x = -0.6 Simplifying x = -0.6
| n+4-6n=-10-6n+5+2n | | 3y-3=2y+6 | | v^2-7v=18 | | 1+4/2=7 | | 4x+9=36 | | 6x^2+9x+6=0 | | -2(8-5a)-a=3a+8 | | 21=(3+2)y | | 5=5t^2-16t+3 | | 18x+17-23x=14-11x-15 | | 2-10k=2k+26 | | 0+3y=11 | | 21=2(y+3) | | -(-85)= | | -4*5=b | | w^2-6w=27 | | 8+3y=11 | | v=1*w*h | | -x-20=-3x+8 | | 8+(3)(0)=11 | | -14-4x=12-2x | | 4+3=n | | x^4=x-6 | | 2(x-9)+1=3(x-3) | | 5+2x=-5 | | -29-x=37+5x | | -[-44]= | | 4e^3x-1.5=360 | | -15+2x=-3x+15 | | (6x-9)(6x-9)=36x-81 | | -48+5x=51-6x | | 6x+9=11-2x |